A Unique "Composite" PTLD with Diffuse Large B-Cell and T/Anaplastic Large Cell Lymphoma Components Occurring 17 Years after Transplant. (7th May 2013) - La Fortune, Kristin; Zhang, Dahua; Raca, Gordana; Ranheim, Erik A.
Abstract : Posttransplant lymphoproliferative disorder (PTLD) comprises a spectrum ranging from polyclonal hyperplasia to aggressive monoclonal lymphomas. The majority of PTLDs are of B-cell origin while T-cell PTLDs and Hodgkin lymphoma-like PTLDs are uncommon. Here, we report a unique case of a 56-year-old man in whom a lymphoma with two distinct components developed as a duodenal mass seventeen years following a combined kidney-pancreas transplant. This PTLD, which has features not previously reported in the literature, consisted of one component of CD20 positive and EBV negative monomorphic diffuse large B-cell lymphoma. The other component showed anaplastic morphology, expressed some but not all T-cell markers, failed to express most B-cell markers except for PAX5, and was diffusely EBV positive. Possible etiologies for this peculiar constellation of findings are discussed and the literature reviewed for "composite-like" lymphomas late in the posttransplant setting.